Isolation and Structure Determination of Antioxidants Active Compounds from Ethyl Acetate Extract of Heartwood Namnam (Cynometra cauliflora L.) - Dede Sukandar; Siti Nurbayti; Tarso Rudiana; Tsalats Wahyul Husna (Jurnal Kimia Terapan Indonesia, 2017)
Active compounds with antioxidant activity were isolated from ethyl acetate extract of namnam stem (C. cauliflora L.) that had undergone maceration and fractionation by gravity column chromatography. The compounds were later identified by by using UV-Vis Spectrophotometry, FTIR, LCMS and 1H-NMR. Ethyl acetate extract of namnam stem showed considerably high antioxidant activity (IC50 value 4.68 ± 0.035 ppm). The results of analysis by UV-Vis and FTIR showed carbonyl group conjugated with an aromatic ring at band I (λmax 330.22 nm), chromophore group of alkene (C=C) at band II (λmax 268.67 nm) and functional groups such as O−H (3343.91 cm-1), C=O (1729.23 cm-1), C=C (1652.64 and 1611.99 cm-1), C−O (1269.89) and C−H ortho (738.23 cm-1). LCMS (m/z 270.9246) and 1H-NMR data showed seven proton signals on the aromatic ring at carbon position C-3 at δH 6.86 ppm (1H, s), C-6 at δH 5.95 ppm (1H, d, J=1.95 Hz), C-8 at δH 6.25 ppm (1H, d, J= 1.95 Hz), C-2’ and C-6’ at δH 7.03 ppm (2H, d, J=7.87 Hz), C-3’ and C-5’ at δH 6.87 ppm (2H, d, J= 7.87 Hz) so that the structure was identified as a flavonoid which was 4 ', 5,7-trihydroxy-flavones or known as apigenin. The isolated apigenin had very strong antioxidant activity, as shown by IC50 value of 5.18 ± 0.014 ppm.